Implementation of Direct Instruction Based on Formative Assessment with Chunking Technique to Improve Students’ Understanding of Basic Economic Concepts in Semester I - Diyaa Aaisyah Salmaa Putri Atmaja; Mad Yusup; Elfreda Aplonia Lau; Ida Rosanti; Purbawati Purbawati; Titin Ruliana (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
In this classroom context, several first-year students showed difficulty maintaining learning focus when basic economic concepts were delivered through long and continuous oral explanations. This classroom condition created challenges in Introduction to Economics, a conceptual course that requires students to understand abstract and interrelated concepts. This study aimed to improve student's understanding of basic economic concepts through the implementation of Direct Instruction integrated with formative assessment using a chunking technique. A Classroom Action Research design was employed in two cycles involving 19 first-semester Industrial Engineering students at Universitas Nahdlatul Ulama Kalimantan Timur. Learning materials were presented in small, sequential conceptual units, and each unit was followed by formative assessment and immediate feedback. Data were analyzed descriptively by comparing class mean scores, the number and percentage of students achieving the minimum mastery criteria, and observed changes in student’s learning engagement. The results showed a positive improvement in the local classroom context. The percentage of students achieving the minimum mastery criteria increased from only 15.8% in the pre-action stage to 36.8% in Cycle I and 84.2% in Cycle II, with the average score of class rising from 34.3 in pre-action stage to 59.8 in Cycle I and 83.8 in Cycle II and average score of students who achieved mastery rising from 70.6 in pre-action stage to 77.4 in Cycle I and 88.8 in Cycle II. Students also demonstrated better focus, more active participation, and reduced anxiety during the learning process. These findings indicate that Direct Instruction combined with chunking and formative assessment has practical potential to support the improvement of basic economic concept learning in the class studied.